Systematic and meta-based evaluation of the relationship between the built environment and physical activity behaviors among older adults - You,Yanwei; Chen,Yuquan; Zhang,Qi; Hu,Xiaojie; Li,Xingzhong; Yang,Ping; Zuo,Qun; Cao,Qiang (PeerJ, 2023)
Objectives Existing assertions about the relationship between various factors of the built environment and physical activity behaviors are inconsistent and warrant further exploration and analysis. Methods This study systematically searched PubMed, Embase, Web of Science, Scopus, the Cochrane Library and Google Scholar for the effect of the built environment on the physical activity behaviors of older adults. R software was used to calculate the meta-estimated odds ratio with a 95% confidence interval. Simultaneously, the quality of included studies was evaluated using an observational study quality evaluation standard recommended by American health care quality and research institutions. Results A total of 16 original researches were included in this meta-analysis and eight factors of the built environment were evaluated. These factors which ranked from high to low according to their impact were traffic safety (OR = 1.58, 95% CI [1.14–2.20]), destination accessibility (OR = 1.24, 95% CI [1.06–1.44]), aesthetics of sports venues (OR = 1.21, 95% CI [1.07–1.37]), virescence of sports venues (OR = 1.14, 95% CI [1.06–1.23]), building density (OR = 1.07, 95% CI [1.02–1.13]). Additionally, it seemed that there was no potential association between mixed land use (OR = 1.01, 95% CI [0.92–1.10]), the quality of pedestrian facilities (OR = 1.00, 95% CI [0.92–1.08]) or commercial facilities (OR = 0.94, 95% CI [0.88–1.00]) and physical activity behaviors of older adults. Conclusions The built environment has been found to exhibit a significant relationship with the physical activity behaviors of older adults. It is proposed that factors such as traffic safety, destination accessibility, aesthetics of sports venues, virescence of sports venues, and building density be given more consideration when aiming to promote physical activity levels among older adults.
Keywords: Physical activity behaviors; Built environment; Elderly; Social-ecological model; Systematic review; Meta-analysis